High-transparency nano-modified degradable filling master batch produced by special anhydrous sodium sulphate and preparation method of high-transparency nano-modified degradable filling master batch

By designing a special Yuanming powder to produce highly transparent nanomodified degradable filler masterbatch and its preparation method, the problems of poor tensile strength and insufficient transparency of the existing film are solved, and the improvement of high transparency and strength is achieved. Saved energy.

CN119410049AInactive Publication Date: 2025-02-11SC HONGYA QINGYIJIANG SODIUM SULPHATE CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411522088.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The tensile strength of existing PE and PP films for packaging is poor, and the transparency is average, which cannot meet the needs of high transparency.

Method used

Design a special Yuanming powder to produce highly transparent nanomodified degradable filler and its preparation method. By mixing Yuanming powder, high-pressure polyethylene PE, cellulose nanocrystals and nanocrystalline particles in a specific proportion, and Heating and mixing and twin-screw extrusion molding are carried out in a high-temperature mixer.

Benefits of technology

It significantly improves the tensile strength and transparency of the film, can meet the needs of high transparency, saves energy, avoids material solidification, and improves the extrusion effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410049A_ABST
    Figure CN119410049A_ABST
Patent Text Reader

Abstract

The invention relates to a high-transparency nano-modified degradable filling master batch produced by special anhydrous sodium sulphate and a preparation method of the high-transparency nano-modified degradable filling master batch. The high-transparency nano-modified degradable filling master batch is prepared from 65%-70% of anhydrous sodium sulphate, 10%-15% of high-pressure polyethylene PE, 5%-10% of cellulose nanocrystalline and 5%-20% of nanocrystalline particles. Due to the fact that the cellulose nanocrystals have high transparency and glossiness, and the molten cellulose nanocrystals have highly-ordered crystalline structures, the capacity of resisting external acting force is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium sulphate production, in particular to a highly transparent nano-modified degradable filling masterbatch produced by special sodium sulphate production and a preparation method thereof. Background Art

[0002] PE film, or polyethylene film, refers to a film produced with PE film. PE film has the advantages of moisture resistance and low moisture permeability. The output of plastic film in China accounts for about 20% of the total output of plastic products, and is one of the categories with the fastest output growth among plastic products. From the application field of China's plastic film (thickness of 0.06mm to 0.26mm), the packaging industry has the largest amount, the most varieties, and the widest application, accounting for about 2 / 3 of its consumption, followed by agriculture, accounting for about 30%, and then functional films, such as microporous films, shielding films, geomembranes, etc. With the development of China's economy and the adjustment of rural industrial structure, the market demand for plastic films in all walks of life in China continues to rise. China's plastic film industry is in a stage of vigorous development. It is reported that the demand for plastic films in China will grow at a rate of more than 9% every year. Moreover, with the continuous emergence of various new materials, new equipment and new processes, China's plastic films will be driven to develop in the direction of diversified varieties, specialization and multifunctional composite films.

[0003] However, the tensile strength of PE and PP films for packaging prepared with existing materials is poor and needs to be improved. In addition, the transparency of PE and PP films prepared with existing materials is average and cannot meet the demand for high transparency.

[0004] Therefore, we propose a special sodium sulfate to produce highly transparent nano-modified biodegradable filler masterbatch and its preparation method, which improves the tensile strength and transparency of the film and can be widely used in packaging films of various PE and PP films, industrial films, etc. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, meet the actual needs, and provide a special sodium sulfate production high-transparency nano-modified biodegradable filling masterbatch and its preparation method to solve the current existing packaging PE, PP film, the tensile strength is poor, there is room for improvement. In addition, the transparency of PE, PP films made of traditional materials is general and cannot meet the technical problems of high transparency requirements.

[0006] In order to achieve the purpose of the present invention, the technical scheme adopted by the present invention is: designing a special sodium sulfate production high-transparent nano-modified biodegradable filling masterbatch and its preparation method, sodium sulfate 65%-70%, high-pressure polyethylene PE 10%-15%, cellulose nanocrystals 5%-10%, nano-microcrystalline particles 5%-20%.

[0007] Preferably, 65% sodium sulfate, 10% high-pressure polyethylene PE, 5% cellulose nanocrystals, and 20% nano-microcrystalline particles.

[0008] Preferably, sodium sulphate 66%, high pressure polyethylene PE 11%, cellulose nanocrystals 6%, and nano-microcrystalline particles 17%.

[0009] Preferably, the composition includes 67% sodium sulfate, 12% high pressure polyethylene PE, 7% cellulose nanocrystals and 14% nano-crystal particles.

[0010] Preferably, sodium sulfate 68%, high pressure polyethylene PE 14%, cellulose nanocrystals 8%, and nano-microcrystalline particles 10%.

[0011] Preferably, the composition comprises 70% sodium sulfate, 15% high pressure polyethylene PE, 10% cellulose nanocrystals and 5% nano-microcrystalline particles.

[0012] Preferably, a special sodium sulfate is used to produce a highly transparent nano-modified degradable filler masterbatch and a preparation method thereof, and the steps of using the special sodium sulfate as described in claims 1-7 to produce a highly transparent nano-modified degradable filler masterbatch and a preparation method thereof are as follows:

[0013] S1. First, grind the sodium sulphate into 2-4 micron powder through ultrafine powder grinding equipment;

[0014] S2, then pouring high-pressure polyethylene PE, cellulose nanocrystals, nano-microcrystalline particles and additives into a high-temperature mixer for heating and mixing, an air suction pump is provided in the high-temperature mixer, a ventilation pipe is connected to the surface of the air suction pump, and the ventilation pipe is connected to the twin-screw extruder;

[0015] S3. After the heating and kneading is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The present invention can combine cellulose nanocrystals with materials by using cellulose nanocrystals. Since cellulose nanocrystals themselves have high transparency and glossiness, and molten cellulose nanocrystals have a highly ordered crystalline structure, they have a strong ability to resist external forces. At the same time, their shape and size can be controlled to meet the needs of different uses. The crystalline structure of cellulose nanocrystals can be directly changed to reduce the friction coefficient of the surface, and the transparency of the material can be further improved while improving the strength of the material.

[0018] 2. The present invention combines nano-crystal particles with materials. Nano-crystal particles refer to crystals in which each crystal grain is composed of only thousands or tens of thousands of unit cells placed side by side. The surface of the crystallite is large, and the surface adsorption performance and surface activity are quite outstanding. By utilizing the nano-scale contacts of high-purity nano-crystal particles, when mixing in a mixture, hundreds of channels with an area of ​​several square millimeters can be opened in the mixture for cellulose nano-crystals to pass through, thereby making the cellulose nano-crystals uniformly dispersed in the mixture. At the same time, during the crystallization process of PE material, crystals can also pass through hundreds of channels, making the crystals uniformly dispersed, avoiding crystal accumulation and affecting the transparency of alum.

[0019] 3. The present invention provides an air suction pump in the high-temperature mixer, and a ventilation duct is connected to the surface of the air suction pump, and the ventilation duct is connected to the twin-screw extruder. Before and during the extrusion of the alum, the high-temperature hot air generated in the high-temperature mixer can be drawn into the twin-screw extruder to heat the material. No additional heating equipment is required, which saves energy and avoids pre-cooling and solidification of the material in the twin-screw extruder, which affects the extrusion effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the preparation process of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings and embodiments:

[0022] A special sodium sulfate production of highly transparent nano-modified biodegradable filler masterbatch and its preparation method, see Figure 1 , sodium sulfate 65%-70%, high pressure polyethylene PE 10%-15%, cellulose nanocrystals 5%-10%, nano-microcrystalline particles 5%-20%.

[0023] For details, see Figure 1 , 65% sodium sulfate, 10% high-pressure polyethylene PE, 5% cellulose nanocrystals, and 20% nano-microcrystalline particles.

[0024] For further information, see Figure 1 , sodium sulphate 66%, high pressure polyethylene PE 11%, cellulose nanocrystals 6%, nano-microcrystalline particles 17%.

[0025] It is worth noting that see Figure 1 , 67% alum, 12% high-pressure polyethylene PE, 7% cellulose nanocrystals, and 14% nano-microcrystalline particles.

[0026] It is worth noting that see Figure 1 , sodium sulfate 68%, high pressure polyethylene PE 14%, cellulose nanocrystals 8%, nano-microcrystalline particles 10% 5%.

[0027] It is worth mentioning that see Figure 1 , sodium sulphate 70%, high pressure polyethylene PE 15%, cellulose nanocrystals 10%, nano-microcrystalline particles 5%.

[0028] A special sodium sulfate for producing highly transparent nano-modified degradable filler masterbatch and a preparation method thereof, wherein the steps of producing highly transparent nano-modified degradable filler masterbatch and a preparation method thereof using the special sodium sulfate as claimed in claims 1 to 7 are as follows:

[0029] S1. First, grind the sodium sulphate into 2-4 micron powder through ultrafine powder grinding equipment;

[0030] S2, then pouring high-pressure polyethylene PE, cellulose nanocrystals, and nano-microcrystalline particle additives into a high-temperature mixer for heating and mixing, and providing an air pump in the high-temperature mixer, connecting a ventilation pipe on the surface of the air pump, and connecting the ventilation pipe to the twin-screw extruder;

[0031] S3. After the heating and kneading is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

[0032] In the present invention:

[0033] Cellulose nanocrystals are nanoscale materials extracted from natural cellulose (such as wood, cotton, flax and other plant fibers) with excellent physical, chemical and biological properties. These properties make cellulose nanocrystals have a wide range of application potentials in the food industry.

[0034] Nanocrystal particles (including cellulose nanocrystals, etc.) can be used in food. Nanocrystal particles can also be used in the manufacture of food packaging materials, such as antibacterial packaging films, degradable packaging materials, etc., to improve the safety and environmental protection of food.

[0035] Embodiment 1

[0036] The special sodium sulfate production highly transparent nano-modified degradable filling masterbatch and its preparation method include the following raw materials and their proportions: sodium sulfate 65%, high-pressure polyethylene PE 10%, cellulose nanocrystals 5%, nano-microcrystalline particles 20%;

[0037] A special sodium sulfate production of highly transparent nano-modified biodegradable filling masterbatch and its preparation method The steps of the preparation method are as follows:

[0038] S1. First, grind 65% sodium sulfate into 2-4 micron powder through ultrafine powder grinding equipment;

[0039] S2, then pour 10% high-pressure polyethylene PE, 5% cellulose nanocrystals, 20% nano-microcrystalline particles and additives into a high-temperature mixer for heating and mixing, and an air suction pump is provided in the high-temperature mixer, and a ventilation pipe is connected to the surface of the air suction pump, and the ventilation pipe is connected to the twin-screw extruder;

[0040] S3. After the heating and kneading is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

[0041] Embodiment 2

[0042] The special sodium sulfate production highly transparent nano-modified degradable filling masterbatch and its preparation method include the following raw materials and their proportions: sodium sulfate 66%, high-pressure polyethylene PE 11%, cellulose nanocrystals 6%, nano-microcrystalline particles 17%, etc.

[0043] The steps of producing a highly transparent nano-modified degradable filling masterbatch from a special sodium sulfate and a preparation method thereof are as follows:

[0044] S1. First, grind 66% sodium sulfate into 2-4 micron powder through ultrafine powder grinding equipment;

[0045] S2, then pour 11% high-pressure polyethylene PE, 6% cellulose nanocrystals, 17% nano-microcrystalline particles and additives into a high-temperature mixer for heating and mixing, and an air pump is provided in the high-temperature mixer, and a ventilation pipe is connected to the surface of the air pump, and the ventilation pipe is connected to the twin-screw extruder;

[0046] S3. After the heating and kneading is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

[0047] Embodiment 3

[0048] The special sodium sulfate production highly transparent nano-modified degradable filling masterbatch and its preparation method include the following raw materials and their proportions: sodium sulfate 67%, high-pressure polyethylene PE 12%, cellulose nanocrystal 7%, nano-microcrystalline particles 14%.

[0049] The steps of producing a highly transparent nano-modified degradable filling masterbatch from a special sodium sulfate and a preparation method thereof are as follows:

[0050] S1. First, grind 67% sodium sulfate into 2-4 micron powder through ultrafine powder grinding equipment;

[0051] S2, then pour 12% high pressure polyethylene PE, 7% cellulose nanocrystals, 14% nano-microcrystalline particles and additives into a high-temperature mixer for heating and mixing, and an air pump is arranged in the high-temperature mixer, and a ventilation pipe is connected to the surface of the air pump, and the ventilation pipe is connected to the twin-screw extruder;

[0052] S3. After the heating and kneading is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

[0053] Embodiment 4

[0054] The special sodium sulfate production highly transparent nano-modified degradable filling masterbatch and its preparation method include the following raw materials and their proportions: sodium sulfate 68%, high pressure polyethylene PE 14%, cellulose nanocrystal 8%, nano-microcrystalline particles 10%.

[0055] The steps of producing a highly transparent nano-modified degradable filling masterbatch from a special sodium sulfate and a preparation method thereof are as follows:

[0056] S1. First, grind 68% sodium sulfate into 2-4 micron powder through ultrafine powder grinding equipment;

[0057] S2, then pour 14% high-pressure polyethylene PE8% cellulose nanocrystals, 10% nano-microcrystalline particles and additives into a high-temperature mixer for heating and mixing, and an air suction pump is arranged in the high-temperature mixer, and a ventilation pipe is connected to the surface of the air suction pump, and the ventilation pipe is connected to the twin-screw extruder;

[0058] S3. After the heating and kneading is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

[0059] Embodiment 5

[0060] The special sodium sulfate production highly transparent nano-modified degradable filling masterbatch and its preparation method include the following raw materials and their proportions: sodium sulfate 70%, high pressure polyethylene PE 15%, cellulose nanocrystal 10%, nano-microcrystalline particles 5%.

[0061] The steps of producing a highly transparent nano-modified degradable filling masterbatch from a special sodium sulfate and a preparation method thereof are as follows:

[0062] S1. First, grind 70% of sodium sulphate into 2-4 micron powder through ultrafine powder grinding equipment;

[0063] S2, then pour 15% high-pressure polyethylene PE, 10% cellulose nanocrystals, 5% nano-microcrystalline particles and additives into a high-temperature mixer for heating and mixing, and an air suction pump is provided in the high-temperature mixer, and a ventilation pipe is connected to the surface of the air suction pump, and the ventilation pipe is connected to the twin-screw extruder;

[0064] S3. After the heating and kneading is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

[0065] The data parameters of a traditional special sodium sulfate production of highly transparent nano-modified biodegradable filler masterbatch and its preparation method are shown in Table 1:

[0066] Test items transparency Tensile Strength Dispersion Parameters Low Low Low

[0067] Example 1 A special sodium sulfate production of highly transparent nano-modified degradable filling masterbatch and its preparation method Data parameters

[0068] Table 2 is as follows:

[0069] Test items transparency Stretching effect Dispersion Parameters middle Low generally

[0070] Example 2 A special sodium sulfate production of highly transparent nano-modified degradable filler masterbatch and its preparation method Data parameters

[0071] Table 3 is as follows:

[0072] Test items transparency Stretching effect Dispersion Parameters high generally good

[0073] Example 3 A special sodium sulfate production of highly transparent nano-modified degradable filling masterbatch and its preparation method Data parameters

[0074] Table 4 is as follows:

[0075]

[0076]

[0077] Example 4 A special sodium sulfate production of highly transparent nano-modified degradable filling masterbatch and its preparation method Data parameters

[0078] Table 5 is as follows:

[0079] Test items transparency Stretching effect Dispersion Parameters Very high excellent excellent

[0080] Example 5 A special sodium sulfate production of highly transparent nano-modified degradable filler masterbatch and its preparation method Data parameters

[0081] Table 6 is as follows:

[0082] Test items transparency Stretching effect Dispersion Parameters Very high Excellent excellent

[0083] In summary, referring to the data comparison of Table 1, Table 2, Table 3, Table 4, Table 5 and Table 6, it can be obtained that by using cellulose nanocrystals, cellulose nanocrystals can be combined with materials. Since cellulose nanocrystals themselves have a high degree of transparency and glossiness, and molten cellulose nanocrystals have a highly ordered crystalline structure, they have a strong ability to resist external forces. At the same time, their shape and size can be controlled to meet the needs of different uses. The crystalline structure of cellulose nanocrystals can be directly changed to reduce the surface friction coefficient. While improving the material strength, the transparency of the material can be further improved. Since nano-microcrystalline particles are combined with materials, nano-microcrystalline particles refer to crystals in which each grain is composed of only thousands or tens of thousands of unit cells juxtaposed. The surface of the microcrystal is large, and the surface adsorption performance and surface activity are quite outstanding. By using high-purity The nano-scale contacts of the nano-crystal particles can open hundreds of channels in the area of ​​several square millimeters in the mixture during mixing, for the cellulose nanocrystals to pass through, so that the cellulose nanocrystals are evenly dispersed in the mixture. At the same time, during the crystallization process of the PE material, the crystals can also pass through hundreds of channels, so that the crystals are evenly dispersed, avoiding crystal accumulation and affecting the transparency of the filling masterbatch. An air suction pump is arranged in the high-temperature mixer, and the ventilation pipe is connected to the surface of the air suction pump, and the ventilation pipe is connected to the twin-screw extruder. Before and during the extrusion of the alum, the high-temperature hot air generated in the high-temperature mixer can be drawn into the twin-screw extruder to heat the material. No additional heating equipment is required, which saves energy and avoids the pre-cooling and solidification of the material in the twin-screw extruder, which affects the extrusion effect.

[0084] In addition, the components designed in the present invention are all universal standard parts or components known to technical personnel in this field. Their structures and principles can be known to technical personnel through technical manuals or through conventional experimental methods. They can be fully implemented by technical personnel in this field. Needless to say, the content protected by the present invention does not involve improvements to internal structures and methods.

[0085] The embodiments of the present invention disclose preferred embodiments, but are not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.

Claims

1. A special sodium sulfate production highly transparent nano-modified degradable filler masterbatch and its preparation method, characterized in that: Sodium sulfate 65%-70%, high pressure polyethylene PE 10%-15%, cellulose nanocrystals 5%-10%, nano-microcrystalline particles 5%-20%.

2. A special sodium sulfate production highly transparent nano-modified degradable filler masterbatch and its preparation method as claimed in claim 1, characterized in that: Sodium sulfate 65%, high pressure polyethylene PE 10%, cellulose nanocrystals 5%, nano-microcrystalline particles 20%.

3. The method for preparing a highly transparent nano-modified degradable filler masterbatch made of special sodium sulfate according to claim 1, characterized in that: Sodium sulfate 66%, high pressure polyethylene PE 11%, cellulose nanocrystals 6%, nano-microcrystalline particles 17%.

4. The method for preparing a highly transparent nano-modified degradable filler masterbatch made of special sodium sulfate according to claim 1, characterized in that: Sodium sulfate 67%, high pressure polyethylene PE 12%, cellulose nanocrystals 7%, nano-microcrystalline particles 14%.

5. The method for preparing a highly transparent nano-modified degradable filler masterbatch made of special sodium sulfate according to claim 1, characterized in that: Sodium sulfate 68%, high pressure polyethylene PE 14%, cellulose nanocrystals 8%, nano-microcrystalline particles 10%.

6. A special sodium sulfate production highly transparent nano-modified degradable filler masterbatch and its preparation method as claimed in claim 1, characterized in that: Sodium sulfate 70%, high pressure polyethylene PE 15%, cellulose nanocrystals 10%, nano-microcrystalline particles 5%.

7. A special sodium sulfate production of highly transparent nano-modified degradable filler masterbatch and its preparation method, using the special sodium sulfate production of highly transparent nano-modified degradable filler masterbatch and its preparation method as described in claims 1-7, a special sodium sulfate production of highly transparent nano-modified degradable filler masterbatch and its preparation method The steps of the preparation method are as follows: S1. First, grind the sodium sulphate into 2-4 micron powder through ultrafine powder grinding equipment; S2, then pouring high-pressure polyethylene PE, cellulose nanocrystals, nano-microcrystalline particles and additives into a high-temperature mixer for heating and mixing, an air suction pump is provided in the high-temperature mixer, a ventilation pipe is connected to the surface of the air suction pump, and the ventilation pipe is connected to the twin-screw extruder; S3. After the heating and mixing is completed, the mixture is poured into a twin-screw extruder for granulation and forming into small particles, thereby obtaining a special sodium sulfate production high-transparency nano-modified biodegradable filling masterbatch and its preparation method. During the extrusion process, the air pump inputs the heat generated in the high-temperature mixer into the twin-screw extruder through the ventilation pipe to heat the mixture.

Citation Information

Patent Citations

  • Method for preparing anhydrous sodium sulfate plastic modified master batch

    CN101293967A

  • Polyolefin complete transparent master batch and preparation thereof

    CN101348005A

  • Sodium sulfate plastic filling modified transparent masterbatch

    CN104974426A

  • Sodium sulfate-modified plastic filling masterbatch and preparation method thereof

    CN105968531A

  • Plastic filling masterbatches modified with anhydrous sodium sulphate and preparation method of plastic filling masterbatches

    CN106146974A